2012
DOI: 10.3141/2272-07
|View full text |Cite
|
Sign up to set email alerts
|

Regional Impact of Roadway Construction on Traffic Operations

Abstract: The objective of this study was to develop a methodology for assessing the impact of road construction that could be used to (a) predict the network-level impact of road construction projects, (b) identify critical roadway segments and corridors in which the impacts of construction are expected to be the most severe, and (c) compare alternative construction scenarios and schedules. Dynamic traffic assignment formed the basis of an approach to assess the regional impact of road construction and compare alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Some researchers have developed different methods to predict and evaluate the impact of construction on traffic operation, such as dynamic traffic assignment [27], a five-parameter logistic model that describes the speed-density relationship [22], an optimal nonlinear fitting theory [28], traffic speed versus flow curves, capacity reduction factors, and free-flow speed reduction factors [29]. A bilevel optimization model was proposed for the purpose of minimizing the total travel time of the affected network, involving a link closure and a proposed alternate route for travelers [30].…”
Section: Predict and Evaluate Methods Of Highway Work Zone Impactmentioning
confidence: 99%
“…Some researchers have developed different methods to predict and evaluate the impact of construction on traffic operation, such as dynamic traffic assignment [27], a five-parameter logistic model that describes the speed-density relationship [22], an optimal nonlinear fitting theory [28], traffic speed versus flow curves, capacity reduction factors, and free-flow speed reduction factors [29]. A bilevel optimization model was proposed for the purpose of minimizing the total travel time of the affected network, involving a link closure and a proposed alternate route for travelers [30].…”
Section: Predict and Evaluate Methods Of Highway Work Zone Impactmentioning
confidence: 99%
“…Kamyab, M. [30] used machine learning to predict the influencing factors of future work areas and found that long-term speed changes are important factors in predicting the impact of work areas on traffic. Pesti, G. [10] developed a method for evaluating the impact of road construction work areas, (a) predicting the network level impact of road construction projects, (b) identifying key sections and corridors with the most severe expected construction impact, and (c) comparing alternative construction plans and schedules. Dynamic traffic allocation forms the basis for evaluating the regional impact of road construction and comparing alternative construction schedule plans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the years, in an effort to alleviate the effects of construction work zones on traffic efficiency, researchers and policymakers in the field of transportation have been exploring various strategies. Some scholars have evaluated the impact of road construction through dynamic traffic allocation and compared alternative construction schedule plans in order to choose the optimal plan to reduce travel delays and improve road capacity [10,11]. Several studies have analyzed the impact of construction work zone length on road capacity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…DTA models have been shown to effectively estimate network impacts of short-and long-term construction projects on area traffic patterns by identifying locations where congestion is prevalent (2). However, DTA models often require extensive computational time and computer memory to run on large urban networks.…”
mentioning
confidence: 99%